Effects of Students’ Language Interpretation on Performance in Mathematics in Selected Secondary Schools in Nakuru North Sub-County Kenya - Wanjiru , Ruthiga D.; Kitainge , Kisilu; Samikwo , Dinah (African Journal of Education,Science and Technology (AJEST), 2021)
Over the years, Performance in Mathematics as echoed by the KCSE results has remained poor. Several involvements have been put into place to address this low students’ performance in Mathematics in KCSE. The Education Ministry has tried to enhance the teaching of mathematics in most schools by introducing projects such as Strengthening Mathematics and Sciences in Secondary Education (SMASSE), in order to advance performance. However, the students’ low performance in Mathematics in KCSE persists. Using this situation as a rationale, this study sought to investigate effect of students’ language interpretation on Mathematics performance. Form 3 students in Nakuru North Sub-County participated in the study. The study adopted the following research questions: How do students’ interpretation of language influence their performance in mathematics? Does understanding of word problems in mathematics influence performance in mathematics? How do students’ analysis of mathematical vocabulary influence performance? Do students’ manipulation of mathematics problems influence performance in mathematics? Mixed methods research methodology was employed in the study where qualitative and quantitative data were collected and analyzed. The study used Quasi-experimental design. The population targeted comprised of all Form 3 students in Nakuru North Sub-County which had a population of 3852 students in the 35 public schools. Sixteen schools with a population of 1462 students formed a sample. Written tests were used to collect data and analyzed using SPSS version 22. The study found that students performed significantly better after they were taught mathematics’ vocabularies than before. This study concluded that good performance in mathematics was highly related to students’ understanding of mathematical vocabulary. The study recommends that Mathematics teachers should put more emphasize on definition of mathematical language when presenting content to learners. The policy makers should also ensure that textbooks for Mathematics had well defined vocabularies to ensure that students understand them.